The Aplication of the Guided Inquiry Model on the Fungi Practicum Activities for the Students’ Science Process Skill - Damayanti, Riska; Mubarok, Ibnul; Indriyanti, Dyah Rini (Journal of Biology Education, 2018)
Zygomycota and Ascomycota Classesare classified as the Fungi Kingdom groups It is needed to hold a practicum activity in the fungi grouping learning. Nevertheless, the tools and materials at school to observe the fungi are inadequate. Therefore, it is necessary to hold a fungi practicum which accompanied with a students worksheet that is able to develop the students’ science process skills so that the teachers and the students are able to achieve the learning objectives of the Fungi material. This study aims to analyze the students' science process skills after the application of guided-inquiry learning model in the fungi practicum activity. The study used pre-experimental design method with one-shot case study design as the research method. Furthermore, the students’ understanding level is obtained based on the results of the students' skill score, such as the ability to observe and to conduct an experiment which able to reach the defined completeness criteria. The result shows that the observation skills score of class X.MIA.1 and class X.MIA.3 were 85% and 91% and the experimental skills score of class X.MIA 1 and class X.MIA.3 were 85.7% and 88.5%. The understanding of fungi material is classified successful in Fungi practicum learning activity due to the classical completeness that reaches above 85%.